Educator incentives and educational triage in rural primary schools - Gilligan, Daniel O.; Karachiwalla, Naureen; Kasirye, Ibrahim; Lucas, Adrienne M.; Neal, Derek (University of Wisconsin Press, 2022)
In low-income countries, primary school student achievement is often far below grade level and dropout rates remain high. Further, some educators actively encourage weaker students to drop out before reaching the end of primary school to avoid the negative attention that a school receives when its students perform poorly on their national primary leaving exams. We report the results of an experiment in rural Uganda that sought to both promote learning and reduce dropout rates. We offered bonus payments to grade six (P6) teachers that rewarded each teacher for the math performance of each of her students relative to comparable students in other schools. This Pay for Percentile (PFP) incentive scheme did not improve overall P6 math performance, but it did reduce dropout rates. PFP treatment raised attendance rates a full year after treatment ended from .56 to .60. In schools with math books, treatment increased these attendance rates from .57 to .64, and PFP also improved performance on test items covered by P6 books. PFP did not improve any measure of attendance, achievement, or attainment in schools without books.